PENGARUH KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PDAM GIRI TIRTA KABUPATEN GRESIK - Ahmad Almahdi; Mei Retno Adiwati (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
Human resources become a factor that greatly affects the success of the company. Thus the company must also have skills in managing human resources as employees who work, because patented human resources will also have a good influence on the work tasks that exist in the company. Research this study aims to examine the impact of communication and work environment on employee performance at PDAM Giri Tirta Kabupaten Gresik. Research in the character of a quantitative approach. The population of this research consisted of 63 employees, the sampling technique was used in the form of saturated sampling, and the entire universe was used as the research sample. We use surveys as a data collection method that is distributed to service and production personnel. Analytical model to analyze the data of the study with the SEM method using the PLS software. Research shows that better communication can improve employee performance at PDAM Giri Tirta Kabupaten Gresik. Then they can increase the performance of employees at PDAM Giri Tirta Kabupaten Gresik in a suitable and good working environment